Approaches to the students’ motivation - Vlasenko, Ludmila; Nikitenko, Olga (My University, 2014)
The research deals with those aspects of learning that are most practical for the effective training of students, one of which is the motivation that makes it possible to increase the interest of students in the learning process, improves their personal research activity and creativity.
Keywords: підходи до навчання; ієрархія потреб; мотивація студентів; teaching approaches; hierarchy of needs; students’ motivation; кафедра ділової іноземної мови та міжнародної комунікації